Enhanced healing of surgical periodontal defects in rats following application of a self‐assembling peptide nanofibre hydrogel. (2nd March 2016) - Takeuchi, Takahiro; Bizenjima, Takahiro; Ishii, Yoshihito; Imamura, Kentaro; Suzuki, Eiichi; Seshima, Fumi; Saito, Atsushi
Abstract: Aim: The aim of this study was to investigate the effects of a self‐assembling peptide (SAP) nanofibre hydrogel on healing of surgical periodontal defects in rats. Materials and Methods: In vitro interactions between rat periodontal ligament (PDL) cells and SAP hydrogel (2.5% RADA16) were assessed by cell proliferation assays. In vivo, maxillary first molars of 45 Wistar rats were extracted and after healing, bilateral periodontal defects were surgically created mesially in second molars. Defects were treated with RADA16, Matrigel, or left unfilled. After 2 and 4 weeks, defect healing was evaluated by microcomputed tomography, histological and immunohistochemical analyses. Results: Periodontal ligament cells grown on RADA16 showed an gradual increase in proliferation up to 72 h. At 4 weeks post surgery, the bone volume fraction and trabecular thickness of defect areas in the RADA16 group were significantly greater than those in other groups. Histologically, enhanced new bone formation was observed in the RADA16 group. At 4 weeks, PDL‐like collagen bundles ran oblique to the root surface in the RADA16 group. Expression levels of PCNA‐positive cells, vascular endothelial growth factor and osteopontin in the RADA16 group were significantly greater than those in other groups. Conclusions: Within the limitations of the study, application of the SAP hydrogel promoted healing of surgical periodontal defects by enhancing cell recruitment and possibly angiogenesis.